Microscopic diffusion properties of fixed breast tissue: preliminary findings - Norddin, Narina; Power, Carl; Watson, Geoffrey; Cowin, Gary; Kurniawan, Nyoman; Gluch, Laurence; Bourne, Roger (Wiley, 2014)
Purpose: To investigate the microscopic diffusion properties of formalin-fixed breast tissue. Methods: Diffusion microimaging was performed at 16.4T with 40-mm isotropic voxels on two normal and two cancer tissue samples from four patients. Results were correlated with histology of the samples. Results: Diffusion-weighted images and mean diffusivity maps demonstrated distinct diffusivity differences between breast tissue components. Mean diffusivity (MD) in normal tissue was 0.5960.24 mm2/ms for gland lobule (voxels containing epithelium and intralobular stroma) and 1.2360.34 mm2/ms for interlobular fibrous stroma. In the cancer samples, MD¼0.4560.23 mm2/ms for invasive ductal carcinoma (voxels contain epithelium and intralobular stroma) and 0.6160.35 mm2/ms for ductal carcinoma in situ. There were significant MD differences between all tissue components (P<0.005), except between gland lobule and ductal carcinoma in situ (P¼0.71). The low diffusivity of epithelium-rich cancer tissue and of normal epithelium relative to its supporting fibrous stroma was similar to that reported for prostate tissue and the esophageal wall. Conclusion: Diffusion microimaging demonstrates distinct diffusivity differences between breast tissue glandular structures. Low diffusivity may be a distinctive feature of mammalian epithelia.